Integration of output-based science with the integrated twin tower paradigm in journal review lectures - Jariyah, Ita Ainun; Manan, Abdul; Ummah, Khoirotul (Jurnal Mangifera Edu, 2025)
Integration of knowledge is an interesting phenomenon that has emerged amidst the rapid changes in Islamic religious higher education institutions in Indonesia, which have changed from a State Islamic Religious Institution to a State Islamic University (Universitas Islam Negeri/UIN). The implementation of the integration of knowledge at UIN Sunan Ampel Surabaya refers to the integrated twin-tower model. This study aims to describe the integration of knowledge based on outputs with the integrated twin tower paradigm in journal review lectures. This type of research is qualitative descriptive with the research location of the Science Education Study Program, FTK UINSA, in journal review lectures running in the even semester of the 2022/2023 academic year. Data was collected using documentation, field notes, and questionnaires. Data analysis techniques were carried out using data triangulation techniques, including data reduction, data presentation, and conclusion. The study results showed that lecture planning was carried out well in the semester learning design. Integrating knowledge based on outputs with the integrated twin tower paradigm in journal review lectures went well according to the achievement objectives in the semester learning plan and produced outputs in draft articles. The student’s response to the lectures was positive, resulting in accurate understanding from the students regarding the topics of scientific articles and journals. The lectures had some obstacles but also produced many benefits.